PENGARUH KECERDASAN EMOSIONAL DAN GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP PERFORMANSI KEPALA RA PEREMPUAN DI KABUPATEN PATI - Kamto, Kamto (QUALITY, 2017)
This study aims to menaganlisisi influence of emotional intelligence, and the democratic leadership style to the performance of the head of RA Raudlotul women in Pati regency. Respondents in this study is the head Rayang amounted to 221 people with a sample of 135 people. The analysis used is multiple regression with SPSS 17. Results and discussion shows that 1) The value of correlation (r) of 0.188 indicates the relationship between emotional intelligence and the performance of the head of RA female Raudlatul 2) The value of the correlation (r) of 0.206 indicates a relationship between the democratic leadership and the performance of the head of RA Raudlatul women. 3) Emotional intelligence and the democratic leadership together or simultaneous positive and significant impact on the performance of the head of RA Raudlatul women in Pati regency that F test value of 5.356 and sig. at 0.006. Emotional intelligence means the better and it will be followed democratic leadership performance improvement Raudlatul head Athfal women in Pati regency.